Chronic Kidney Disease and Cerebrovascular Disease: Consensus and Guidance From a KDIGO Controversies Conference. Issue 7 (3rd June 2021) - Kelly, Dearbhla M.; Ademi, Zanfina; Doehner, Wolfram; Lip, Gregory Y.H.; Mark, Patrick; Toyoda, Kazunori; Wong, Christopher X.; Sarnak, Mark; Cheung, Michael; Herzog, Charles A.; Johansen, Kirsten L.; Reinecke, Holger; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : The global health burden of chronic kidney disease is rapidly rising, and chronic kidney disease is an important risk factor for cerebrovascular disease. Proposed underlying mechanisms for this relationship include shared traditional risk factors such as hypertension and diabetes, uremia-related nontraditional risk factors, such as oxidative stress and abnormal calcium-phosphorus metabolism, and dialysis-specific factors such as cerebral hypoperfusion and changes in cardiac structure. Chronic kidney disease frequently complicates routine stroke risk prediction, diagnosis, management, and prevention. It is also associated with worse stroke severity, outcomes and a high burden of silent cerebrovascular disease, and vascular cognitive impairment. Here, we present a summary of the epidemiology, pathophysiology, diagnosis, and treatment of cerebrovascular disease in chronic kidney disease from the Kidney Disease: Improving Global Outcomes Controversies Conference on central and peripheral arterial disease with a focus on knowledge gaps, areas of controversy, and priorities for research.